DAMPAK SEBELUM DAN SESUDAH PEMBANGUNAN PEMBANGKIT LISTRIK TENAGA AIR (PLTA) TERHADAP KONDISI SOSIAL DAN EKONOMI MASYARAKAT DI DESA SULEWANA KECAMATAN PAMONA UTARA KABUPATEN POSO - Kayupa, Olvit Olniwati (Katalogis, 2015)
This study aims to determine how the impact of social and economic impacts as well as differences in socioeconomic levels before and after the construction of hydropower plant in the village of Sulewana, North Pamona district in Poso Regency.The type of analysis in this research is quantitative descriptive analysis. There were 80 people in Sulewana Village involved in this study as the respondents, and the data were obtained by interview and respondents filled the questionnaires. Then, the data were analysed by SPSS software throughÂ t-test paired sample test. The result of this study shows that social conditions which are include education, health and safety level as well as economic conditions that include income level, the level of employment and the welfare level have significant and positive impact on the local development. The indicators were analysed by t-test showsthat there are correlation between the existence of hydropower before and after construction by 0793 or 79.30%.It can also be seen from the significant t value (0.000 <0.05 ) and then the hypothesis is accepted. Thus, the social and economic have an impacton the level of social and economicof Sulewana villagers after the construction of hydropower.